Synthesis and Characterization of Rubber Seed Shell-Derived Activated Carbon by KOH Activation - Gabriela Elsandika; Budi Hariyanto; Panggabean, Lady M.; Sihombing, Feridah A.; Hakim, Luqman (INOVASIA, 2024)
This study presents the preparation and characterization of activated carbon derived from rubber seed shells using potassium hydroxide (KOH) activation. The raw material for this investigation was obtained from rubber seed shells collected from local rubber plantations in Palangka Raya. The activation process involved the use of the chemical activator KOH at a 1:1 carbon-to-KOH ratio in 200 mL of distilled water for a duration of 24 hours. X-ray Diffraction (XRD) analysis confirmed that the resulting activated carbon exhibited an amorphous structure, and all Fourier-Transform Infrared Spectroscopy (FTIR) spectra indicated the presence of functional groups in the activated carbon. The activated carbon possessed a porous structure with a surface area and total pore volume of 2.24 m2/g and 0.02 cm3/g, respectively. These findings necessitate further optimization of the activation process to achieve a larger surface area, thus enabling its application in electronic materials, water treatment, and various other fields.